2020
DOI: 10.1007/s13202-020-01036-7
|View full text |Cite
|
Sign up to set email alerts
|

The hydrocarbon prospectivity of the Mesoproterozoic–Paleozoic intracratonic Voltaian Basin, West African Craton, Ghana

Abstract: Neoproterozoic sedimentary basins are increasingly gaining hydrocarbon exploration attention globally following results of significant discoveries in these basins as a result of long, consistent and focused research and exploration efforts. The hydrocarbon prospectivity of the unexplored Mesoproterozoic–Early Paleozoic Voltaian basin is reviewed relative to global Neoproterozoic basins. Like the Voltaian basin of Ghana, global Neoproterozoic basins have experienced similar geological event of glaciation with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The bitumen presence could be evidence of the fact that the limestones of the basin are possible source rocks. Analysis by Abu et al (2021) even further confirmed that the limestones in the north-eastern region of the Voltaian basin are dolomitic and barite bearing due to hydrothermal mineralization of the carbonates (Abu et al, 2021). However, the presence of any biogenic materials (fossils) which may be responsible for the generation of the hydrocarbons behind these oil seeps is yet to be reported.…”
Section: Introductionmentioning
confidence: 90%
“…The bitumen presence could be evidence of the fact that the limestones of the basin are possible source rocks. Analysis by Abu et al (2021) even further confirmed that the limestones in the north-eastern region of the Voltaian basin are dolomitic and barite bearing due to hydrothermal mineralization of the carbonates (Abu et al, 2021). However, the presence of any biogenic materials (fossils) which may be responsible for the generation of the hydrocarbons behind these oil seeps is yet to be reported.…”
Section: Introductionmentioning
confidence: 90%
“…The sedimentary basin in the North African Craton, such as the Triassic Basin, underwent Pan-Cratonic sedimentary filling during the Paleozoic Era, depositing strata from the Cambrian, Ordovician, Silurian, Devonian, and Carboniferous periods. Similar to the entire Sahara Platform, the basin was profoundly influenced by the Caledonian orogeny, resulting in an uneven uplift [64]. Earlier sedimentary layers experienced varying degrees of erosion, leading to a widespread absence of Permian strata in the basin (Figure 5).…”
Section: Basin Sedimentary Fillingmentioning
confidence: 99%
“…During research by Boamah (2017), bitumen was also found in the quartz veins and carbonate rocks of the Buipe quarry (Boamah, 2017). Analysis by Abu et al (2021) further confirmed that the limestones in the north-eastern region of the country are dolomitic and barite bearing due to hydrothermal mineralization of the carbonates (Abu et al, 2021). It is therefore necessary to study the porosities and permeabilities of the rocks within the Volta Basin to ascertain their potential as petroleum reservoir rocks.…”
Section: Introductionmentioning
confidence: 99%